2022
DOI: 10.3389/fnut.2022.865489
|View full text |Cite
|
Sign up to set email alerts
|

Low Carbohydrate Diets for Diabetic Cardiomyopathy: A Hypothesis

Abstract: Elevated blood glucose levels, insulin resistance (IR), hyperinsulinemia and dyslipidemia the key aspects of type 2 diabetes mellitus (T2DM), contribute to the development of a certain form of cardiomyopathy. This cardiomyopathy, also known as diabetic cardiomyopathy (DMCM), typically occurs in the absence of overt coronary artery disease (CAD), hypertension or valvular disease. DMCM encompasses a variety of pathophysiological processes impacting the myocardium, hence increasing the risk for heart failure (HF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 110 publications
(168 reference statements)
0
9
0
Order By: Relevance
“…Among these recommendations is an emphasis on properly adjusting caloric intake and eating unprocessed poultry, fresh fish, nuts, legumes and a variety of vegetables. Indeed, the substitution of red and processed meat has been associated with a lower risk of total mortality and cardiovascular deaths [16,44,45]. Two to three servings of fish per week have been shown to be associated with lower mortality from any cause or lower risk of HF [46].…”
Section: Non-pharmacological Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these recommendations is an emphasis on properly adjusting caloric intake and eating unprocessed poultry, fresh fish, nuts, legumes and a variety of vegetables. Indeed, the substitution of red and processed meat has been associated with a lower risk of total mortality and cardiovascular deaths [16,44,45]. Two to three servings of fish per week have been shown to be associated with lower mortality from any cause or lower risk of HF [46].…”
Section: Non-pharmacological Treatmentmentioning
confidence: 99%
“…Two to three servings of fish per week have been shown to be associated with lower mortality from any cause or lower risk of HF [46]. In addition, it is recommended to limit consumption of sweetened beverages and highly processed foods containing high amounts of salt and to reduce or stop alcohol consumption [44,45]. The most common diets considered in patients with DM are the Dietary Approaches to Stop Hypertension (DASH) diet, the Mediterranean diet and the vegetarian/vegan diet.…”
Section: Non-pharmacological Treatmentmentioning
confidence: 99%
“…Regarding LC diets, studies have provided controversial results [ 58 ]; however, there is evidence supporting their role in achieving better glycemic control and reduced insulin resistance. These effects contribute to a more favorable metabolic environment that could prevent the development of diabetic cardiomyopathy [ 59 ].…”
Section: Lifestyle Interventionsmentioning
confidence: 99%
“…Therefore, the Mediterranean diet is suggested to play a significant role in reducing risk factors for heart disease, such as obesity, dyslipidemia, hypertension and diabetes [ 6 , 63 ]. For DM, in particular, the adoption of the Mediterranean diet has been linked to a reduction in fasting and postprandial glucose levels [ 58 , 59 ]. At the same time, it has been found that diabetic patients who follow the standard Mediterranean diet show lower levels of hemoglobin A1c (HbA1c) and improved insulin resistance [ 64 , 65 ].…”
Section: Lifestyle Interventionsmentioning
confidence: 99%
“…In summary, nutritional ketosis may serve as a cardioprotective alternative energy supply in the failing heart and reduce pathological ventricular remodeling and could serve as a supportive, non-pharmacologic treatment in people with heart failure along current treatments, such as SGLT2 inhibitors ( 103 , 104 ). Long-term use of ketosis should however be tested for safety.…”
Section: Ketogenic Diet In Cardiologymentioning
confidence: 99%